2017
DOI: 10.1097/md.0000000000007589
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization combined with Huaier granule for the treatment of primary hepatic carcinoma

Abstract: To evaluate the safety and efficacy of transarterial arterial chemoembolization (TACE) with gelatin sponge particles (GSPs-TACE) and Huaier granule to treat primary hepatic carcinoma (PHC).A series of 62 patients with PHC were included between June 2009 and December 2011, and randomly assigned to a control (n = 31) or an experimental group (n = 31). The control patients received TACE with 350 to 560 μm GSPs plus lobaplatin chemotherapy. Patients in the experimental group received TACE plus Huaier granule. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Our study suggested that the inconsistent survival effects of previous malignancies should be considered in clinical trial design and recruitment. In most cancer trials, patients with prior cancer diagnosed within a past 5-year interval are excluded from enrolment [15,45,46]. The reasons for the exclusion include the effects on outcomes, unclear adverse effects, tolerance or reduced efficiency of experimental treatments [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that the inconsistent survival effects of previous malignancies should be considered in clinical trial design and recruitment. In most cancer trials, patients with prior cancer diagnosed within a past 5-year interval are excluded from enrolment [15,45,46]. The reasons for the exclusion include the effects on outcomes, unclear adverse effects, tolerance or reduced efficiency of experimental treatments [30].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the herb medicine has been widely used in the treatment of HCC [ 3 5 ]. In our institute, we have a continuous interest in the treatment of HCC with Chinese herbs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huaier granules are a new anti-tumor drug extracted from Trametes robiniophila Murr (Huaier) (Zhao et al, 2017 ). Its main active ingredient is a proteoglycan composed of 41.53% polyose, 12.93% amino acid, and 8.72% H 2 O (Zou et al, 2015 ).…”
Section: Chinese Medicine Preparations For Dsmmentioning
confidence: 99%